ANALISIS PENGARUH PROMOTION MIX TERHADAP BEHAVIOR INTENTION DENGAN RELIGIOUSITY SEBAGAI VARIABEL MODERASI (STUDI PADA KONSUMEN KOSMETIK WARDAH DI KOTA MATARAM) - Hanik Setiyowati; Baiq Handayani Rinuastuti; Akhmad Saufi (Master of Management, Mataram University, 2017)
This research is aimed at analyzing the correlation between promotion mix and behavior intention with regularity as moderating variable of Wardah consumers in Mataram. This research is quantitative study. The populations are women users of Wardah cosmetics in Mataram. the samples are 190 woman respondents selected through purposive sampling. The data were analyzed using Moderated Regression Analysis or interaction test as the hypothesis test with the special multiple linear regression in which the regression equation consists of interactional elements (dual or more multiplication of independent variables).The research showed that promotion mix had some significant effects on the behavior intention which meant that the better the promotion mix, including advertisement, sales promotion, publicity, personal selling, and direct marketing was, the better the behavior intention reflected through loyalty, propensity to switch, willingness to pay more, external response to problem, and internal response to problem was. Religiosity moderated the correlation between promotion mix and behavior intention. This meant that the higher the religiosity was, the stronger the correlation between promotion mix and behavior intention was. Religiosity was a moderating variable that cannot be an independent variable. Keywords: promotion mix, behavior intention, religiousity.